Formulation of mice diet with low cholecalciferol content - Sumariyono; Handayani, Dian; Setiati, Siti; Amalialjinan, Nadia; Abellia, Gaby; Anindyanti, Risma Debby; Dienillah, Syifa Sarah; Ernawati; Tanadi, Caroline (Faculty of Medicine Universitas Indonesia, 2025)
BACKGROUND Vitamin D deficiency has been linked to autoimmune diseases, cancer, and cardiovascular diseases. Although 1 study attempted to elucidate the ingredients required to make this diet, the process remained unclear. Hence, this study aimed to customize a low cholecalciferol diet with good tolerability in mice. METHODS We customized a diet containing a normal cholecalciferol content (1 IU/g diet) and another with a low cholecalciferol content (0.05 IU/g diet). Samples from both diets were sent to an independent laboratory to ensure that the levels of cholecalciferol, phosphorus, and calcium present in the custom diets matched our calculations. 5 mice were fed the customized normal cholecalciferol diet for 1 week to assess tolerability. Tolerability was assessed by measuring the amount of food consumed, weight gained, and the presence of any adverse events. RESULTS Cholecalciferol, phosphorous, and calcium levels in both diets satisfactorily matched our calculations. The diet was well tolerated without any adverse events or mortalities. The mice consumed an adequate amount of food (mean: 5.34 [0.08] g diet/day, 95% confidence interval [CI]: 5.12–5.56; 19.38 kcal, fat: 0.43 g, protein: 0.14 g, carbohydrates: 3.16 g, and cholecalciferol: 0.007 mg) and gained a slight amount of weight by the end of the experiment (mean: 1.86 [0.46] g, 95% CI: 0.58–3.14). CONCLUSIONS This study successfully created 2 custom diets with quantified cholecalciferol contents. This animal model may prove valuable for studies involving vitamin D.